METHODOLOGICAL SUPPORT FOR RESEARCH ON THE FEASIBILITY OF USING HIGH-SPEED TOOL STEEL AS COATINGS IN FRICTION UNITS - Tamargazin, Oleksandr; Pryimak, Liudmyla; Morshch, Illia (Problems of Friction and Wear, 2025)
The paper considers methods of research in the field of composite materials used as surfacing materials. In particular, the modern equipment used in the analysis of experimental samples obtained in the study of the use of tool high-speed steels as a coating applied by vacuum electron beam treatment in order to organize micrometallurgical processes with minimal impact on the base metal and the ability to form a hardened layer whose thickness is adjustable within wide limits is considered.